Book Review: Abdulrahman OSHIOKE ARUNAH, A history of Auchi Kingdom, Ilorin, Haytee Press and Publishing Co. Nig. Ltd, 2010, pp. 368, ISBN 976-8090-25-7 - Yakubu, Suleiman (Eximia, 2022)
Abdulrahman Oshioke Arunah is a retired colonel of the Nigerian army. He holds a Training Support Certificate, an equivalent of a Masters Degree in Educational Technology in Nigeria. Before he joined the Nigerian army in 1972, he was a teacher and taught students at a secondary school. He has a very rich knowledge of the history and cultural practices of the Auchi Kingdom. His professional experience is teaching in a secondary school, Education officer, Chief Instructor, Deputy Commandant of the Nigerian Military School, Executive Secretary of Armed forces Schools Management Board and the Assistant Director of Army Education at the 2nd Mechanised Infantry Division, all in the Nigerian army except his teaching experience in the secondary school. The author consulted lots of archival materials, primary and secondary sources.